Pengaruh Latihan Target terhadap Ketepatan Shooting Pemain Futsal SMP Negeri 13 Kota Malang - Arhiza Dimas Ikhsanuddin; Olivia Andiana (Lembaga Yasin AlSys, 2025)
The shooting ability of futsal extracurricular players at SMP Negeri 13 Malang City, based on initial observations, is still not optimal, partly due to the absence of a structured shooting training program specifically targeting accuracy improvement. This study aimed to analyze the effect of target training on the shooting accuracy of futsal players by designing and implementing a systematic shooting training program. A quantitative approach with a one-group pre-test–post-test experimental design was employed, involving 20 participants selected through purposive sampling based on their active participation in futsal training. Data were collected through shooting tests and analyzed using normality and homogeneity tests as well as a paired samples t-test. The results showed a significant increase in post-test scores compared to pre-test scores, indicating that target training is effective in improving players’ shooting accuracy. These findings affirm that a structured shooting training program makes a tangible contribution to enhancing students’ technical skills, with practical implications for coaches to implement shooting drills continuously and combine them with other futsal technical training, while future research is recommended to incorporate physical and psychological variables to broaden understanding of the factors influencing shooting accuracy.